Current trends and future directions in swan research: insights from the 6th International Swan Symposium - Wood, Kevin A.; Cao, Lei; Clausen, Preben; Ely, Craig R.; LuigujÃµe, Leho; Rees, Eileen C.; Snyder, Jeffrey; Solovyeva, Diana V.; WÅ‚odarczyk, RadosÅ‚aw (Wildfowl, 2019)
Given their popularity with researchers and public alike, together with their welldocumented importance in aquatic and terrestrial ecosystems, fundamental and applied research on swans continues to develop in the 21st century. The 6th International Swan Symposium (6th ISS), was held at the Estonian University of Life Sciences in Tartu, Estonia, in October 2018. The symposium brought together 101 delegates from 17 countries, with presentations on a range of topics on Cygnus and Coscoroba species, including monitoring, habitat and resource use, demography, movements and migration, and threats and conservation. The proceedings of the 6th ISS in this special issue of Wildfowl include select papers on swan research presented at the 6th ISS, covering a wide range of species, systems and issues. This paper presents a synthesis of the 6th ISS and an overview of current trends and future directions in swan research. Despite progress on many topics, southern hemisphere swan species continue to receive less attention than their northern hemisphere counterparts, whilst facing many of the same pressures. It is clear that, given the challenges facing swan researchers in the twenty-first century, international cooperation will continue to be vital. Swans are highly mobile animals and many populations undertake migrations spanning thousands of kilometres, and crucially do not recognise human geographic and political borders. Such international collaborations will be particularly important in coordinating future monitoring and conservation activities. The IUCN-SSC/Wetlands International Swan Specialist Group (SSG) will continue to facilitate international collaborations and communication among the global network of swan researchers, through its activities, website and annual newsletter. Given the substantial challenges and knowledge gaps documented here, there is no doubt that swan researchers will continue to benefit from regular symposia to share information and develop collaborations towards understanding and addressing emerging conservation issues. As such, we recommend holding International Swan Symposia every 4â€“5 years.